# evaluation

• Aug 7th 2009, 11:28 AM
evaluation
when $\displaystyle c=-7$and $\displaystyle d=4$

$\displaystyle \sqrt{d} - dc^2$

$\displaystyle \sqrt{4} - 4 x (-7)^2$

$\displaystyle 2 - 4 x (-7)^2 = -194$

this right?
• Aug 7th 2009, 11:39 AM
Amer
Quote:

when $\displaystyle c=-7$and $\displaystyle d=4$

$\displaystyle \sqrt{d} - dc^2$

$\displaystyle \sqrt{4} - 4 x (-7)^2$

$\displaystyle 2 - 4 x (-7)^2 = -194$

this right?

it is right but $\displaystyle \sqrt{4}=\mp 2$ since $\displaystyle 2^2=4$ and $\displaystyle (-2)^2=4$ so you will have two answers the first one you find it
the second one

$\displaystyle -2-4(-7)^2=-198$
• Aug 7th 2009, 11:42 AM
So are you saying there are two answers?
• Aug 7th 2009, 11:44 AM
Amer
Quote:

So are you saying there are two answers?

yeah
• Aug 7th 2009, 11:45 AM
Ok so i'm not sure what to do now then?
• Aug 7th 2009, 11:52 AM
Amer
Quote:

Ok so i'm not sure what to do now then?

did you know that

$\displaystyle (-2)^2=4$
$\displaystyle (-4)^2=16$
$\displaystyle (-7)^2=49$

so

$\displaystyle \sqrt{4}=\mp 2$
$\displaystyle \sqrt{16}=\mp 4$
$\displaystyle \sqrt{49}=\mp 7$

in general
$\displaystyle \sqrt{a^2}=\mp a$ a is real number

in you question

$\displaystyle \sqrt{4}-4(-7)^2$ have two solutions since $\displaystyle \sqrt{4}=2$ and $\displaystyle \sqrt{4}=-2$

first one
$\displaystyle 2-4(49)=2-196=-194$

second one

$\displaystyle -2-4(49)=-2-196=-198$
• Aug 7th 2009, 12:07 PM
Does the same apply to this formula

$\displaystyle a = -7, b = 4$

$\displaystyle a - b(a + b)$

$\displaystyle (-7) - 4((-7)+4) = 5$
• Aug 7th 2009, 12:10 PM
Amer
Quote:

Does the same apply to this formula

$\displaystyle a = -7, b = 4$

$\displaystyle a - b(a + b)$

$\displaystyle (-7) - 4((-7)+4) = 5$

it is correct
• Aug 7th 2009, 12:20 PM
stapel
Quote:

$\displaystyle \sqrt{d}\, -\, dc^2\, =\,\sqrt{4}\, -\, (4)(-7)^2$
. . .$\displaystyle =\, 2\, -\,4(49)\, =\, 2\, -\, 196\, =\, -194$